Wild and cultivated potato species diversity, taxonomy, and conservation - Peralta, Iris Edith; Clausen, Andrea Martina; Zorrilla, Cinthya; Ames, Mercedes; Digilio, Ariana; Rodriguez, Flor (Springer, 2022)
In the present chapter, we summarize the knowledge of wild and cultivated potato species, diversity, a taxonomic update including group concept classification and description, species valid names, and a complete synonymy, distribution, and habitat. Likewise, the importance of reproductive characters, breeding barriers, interspecific hybridization, and gene flow, introgression, polyploidy in potato evolution and ecological adaptation, and conservation strategies is explained. Also a comprehensive taxonomy of all wild and cultivated potatoes, based on the integration of multiple evidences and phylogenetic relationships between taxa is discussed, providing a framework for further investigation of complex groups as well as rare endemic species. Hypothesis regarding patterns of species diversity and distributions, and adaptive mechanisms to different extreme environments are proposed. More recent genomic approaches are promissory not only to investigate wild potato genome evolution but also to detect alleles related to important agronomic traits. Germplasm of more wild species or potato landraces can be explored considering hypothesis of relationships. A taxonomic framework could be useful for harmonizing names and classification of potato collection among genebanks. The knowledge of species diversity and distribution patterns is fundamental for collecting strategies and the establishment of natural protected areas as well as agrobiodiversity zones, and for management and sustainable use of potato genetic resources.